The Effect of Water Vapor and Humidity on the Topcon Photovoltaic Cell - Abobaker Alansaryi; Abdulgader Alsharif (African Journal of Advanced Pure and Applied Sciences, 2024)
The purpose of the study is to evaluate how water vapor, humidity, rain, moisture, and haze affected the Topcon photovoltaic cell's performance. The study discovered that poor weathering and high humidity have a negative impact on photovoltaic cells' and panels' performance. For instance, haze has a major impact on photovoltaic (PV) power generation. Quantitative studies on the impact of haze on photovoltaic power generation are scarce; however, as fine particulate matter concentrations increase, they become the main factor influencing solar irradiance and drastically reduce PV power generation. Due to the corrosion process, moisture and humidity can also cause photovoltaic cells and panels to deteriorate. Moisture intrusion is at the center of most degradation mechanisms that lead to PV module power degradation. Embedded moisture sensors, desiccant-stacked polyisobutylene sealants, encapsulants with improved moisture barrier and adhesion qualities, and PV designs with or without breathable back sheets are some of the techniques used to stop or reduce moisture ingression in PV modules. The study made several recommendations as well, such as placing the solar energy units at an appropriate inclination angle to maximize solar radiation and prevent the negative effects of rain and humidity, as well as shielding them from bad weather conditions, such as heavy rain and high humidity.